2018
DOI: 10.3390/su10061979
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Connectivity as a Tool in Green Space Evaluation and Optimization of the Haidan District, Beijing

Abstract: The demand for urban construction has placed growing pressure on biodiversity conservation. In China, landscape fragmentation caused by rapid urbanization has resulted in an immense amount of damage to the ecological system. Taking the Haidian District of Beijing as the study area, this study distinguishes the vital patches and corridors for landscape connectivity maintenance through morphological spatial pattern analysis (MSPA), the probability of connectivity (PC), and the least-cost path analysis. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 64 publications
(70 reference statements)
2
20
0
Order By: Relevance
“…Lots of studies have figured out that urbanization has caused the results of landscape fragmentation functionally and structurally [44][45][46]. For instance, landscape fragmentation resulting from urban expansion took place in Haidian District, Beijing, China [21]. In the current study, our results suggest that landscape fragmentation (low asymptotic bio-energy patches in Figure 4b) is occurring in our case study area as a result of rapid urbanization.…”
Section: Landscape Fragmentation Caused By Urbanizationsupporting
confidence: 46%
“…Lots of studies have figured out that urbanization has caused the results of landscape fragmentation functionally and structurally [44][45][46]. For instance, landscape fragmentation resulting from urban expansion took place in Haidian District, Beijing, China [21]. In the current study, our results suggest that landscape fragmentation (low asymptotic bio-energy patches in Figure 4b) is occurring in our case study area as a result of rapid urbanization.…”
Section: Landscape Fragmentation Caused By Urbanizationsupporting
confidence: 46%
“…For example, Psomas et al, based on the SWAT model, simulated and evaluated the impact of different agricultural water management methods in the basin on water-energy-land-food related monitoring indicators, and selected the optimal agricultural water use and management method based on the impact assessment results [45]; Panagopoulos Y et al, evaluated the cost-effectiveness of irrigation and fertilization practices management in reducing agricultural water consumption and surface runoff pollution in different catchment locations to optimize agricultural best management practices(BMPs) selection and allocation, with economic and environmental trade-offs [46]. In addition, some studies make planning decisions based on the integrity of green space structure, mainly using landscape analysis method (using remote sensing data and GIS technology) and non-built-up area design model to improve the landscape connectivity or restore ecological function of green space [47][48][49]. Based on the band protection planning method, the patch-network conceptual planning method and the graph theory method, the green belt around the city [18][19][20], the ecological protection area or the ecological restoration area [13,14,21], the ecological security pattern and the ecological network are constructed [22][23][24].…”
Section: Research On Green Space Utilization and Protection Decision mentioning
confidence: 99%
“…With regard to human disturbance, in riparian areas of Tsing River, bird communities were more sensitive to the number pedestrians and bicycles than that of motorbikes and cars. [60] found that bicycles have more negative effects on birds than pedestrians in parks. Surprisingly, the top 10 birds responded less significantly to the disturbance of pedestrians than the whole bird communities, which may be due to the adaptation of common birds to the urbanized environment with human disturbance.…”
Section: Significant Variables and Implication For Bird Conservationmentioning
confidence: 99%